Effects of three strength training methods on lower extremity strength, jump and sprint performance: a network meta-analysis - Wang, Shaohui; Zhen, Jie; Xiao, Tao (Frontiers in Physiology, 2025)
BackgroundWeightlifting (WT) and Plyometric training (PT) may lead to comparable enhancements in strength, jump, and sprint performance. However, these two training modalities appear to differ significantly in their primary focus and underlying mechanisms.ObjectiveExamining the differences between WT and PT in improving lower extremity sports performance.MethodsA systematic search was conducted from five databases, including Web of Science, PubMed, Scopus, Elsevier, and Springer. Two authors developed specific inclusion and exclusion criteria to screen relevant literature based on the study objectives. The quality of the included studies was assessed using the Physiotherapy Evidence Database (PEDro) scale. We conducted both direct comparisons and network meta-analysis on the eligible studies. The assumptions of similarity, homogeneity, and consistency within the Bayesian network were also confirmed.ResultsA total of 17 studies met the inclusion criteria, involving 394 participants. All studies were found to have a low or moderate risk of bias, with average score of 4.29. The Bayesian network meta-analysis showed no significant differences. According to the SUCRA rankings, TT was most likely to excel in squat jumps (SJ) (SUCRA = 0.76) and maximum strength (SUCRA = 0.95), WT for sprint (SUCRA = 0.77), and PT for countermovement jumps (SUCRA = 0.76). The tests of similarity, homogeneity and consistency of the network meta-analysis were also generally valid. The funnel plot and Egger regression tests indicated no publication bias.ConclusionIn summary, the WT programs are more effective at improving sprint performance by increasing power, while the PT programs improve jumping performance by improving the stretch-shortening cycle.Systematic Review Registrationidentifier CRD 420250540130.